Abbildung der stationären allergologischen Expositionstestungen im deutschen DRG-System - Treudler, Regina; Meier, Florian; Schöffski, Oliver; Simon, Jan (Allergologie, 2012)
Die als Goldstandard geltenden Expositionstestungen auf Medikamente, Nahrungsmittel oder Insektengifte werden in Deutschland zumeist stationär durchgeführt. Seit Einführung der diagnosis-related groups (DRG) im Jahr 2003 sind die Erlöse für diese Testungen einigen Veränderungen unterzogen gewesen. So lag das Relativgewicht zwischen 0,211 und 0,449 und beträgt aktuell 0,381 (2012). Von uns vorgenommene orientierende Überlegungen zum aktuellen Deckungsbeitrag unter Berücksichtigung der Daten des Institutes für das Entgeltsystem im Krankenhaus zeigen, dass für diese allergologischen Leistungen keine adäquate Abbildung im DRG-System vorliegt. Hieraus können sich im Rahmen eines Leistungsprogrammmanagements negative Auswirkungen auf die stationäre allergologische Versorgung ergeben.
WiSo-Import:2015-03-26:4186

Adverse drug events in patients admitted to an emergency department: an analysis of direct costs - Meier, Florian; Maas, Renke; Sonst, Anja; Patapovas, Andrius; Müller, Fabian; Plank-Kiegele, Bettina; Pfistermeister, Barbara; Schöffski, Oliver; Bürkle, Thomas; Dormann, Harald (Pharmacoepidemiology and Drug Safety, 2015)
Purpose Several economic evaluations of adverse drug events (ADEs) exist, but the underlying methodology has not been standardized so far. The aim of the study was to combine prospective, intensive pharmacovigilance methods, and standardized accounting data to calculate direct costs of community-acquired ADEs (caADEs) contributing to emergency department (ED) admission and subsequent hospitalization. Methods A prospective observational study with three phases extending over 2 years was implemented in a 749 bed tertiary care hospital with an annual ED census of approximately 45 000 patients. The patient records of all adult non-trauma ED admissions were systematically analyzed by a team of emergency physicians, clinical pharmacologists, and pharmacists for potential ADE. Associated diagnosis related group costs were extracted from standardized accounting data. Results Of 2262 patients attending the ED during the study periods, the hospitalization of 366 patients (16.2%) was related to one or more caADEs of which 97.5% were considered predictable and 62.0% were classified as preventable. The mean caADE-related diagnosis related group costs were €2743 (95% bias-corrected and accelerated CI: €2498 to €3018). Extrapolated to a national scale, this corresponds to caADE-related costs of €2.245bn for the German health insurance funds, annually. Costs of €1.310bn could be attributed to events classified as predictable and preventable. Conclusions In an ED, caADEs are frequent, and a significant proportion of these events and their related costs appear to be predictable and preventable. The ED as a first-line provider for ADE cases appears to be an appropriate environment to implement strategic and operative improvements for enhanced patient safety.
Keywords: adverse drug event; hospital admission; emergency department; pharmacovigilance; health economics; pharmacoepidemiology

An Analysis of Online Evaluations on a Physician Rating Website: Evidence from a German Public Reporting Instrument - Emmert, Martin; Meier, Florian (Journal of Medical Internet Research, 2013)
Background: Physician rating websites (PRW) have been gaining in popularity among patients who are seeking a physician. However, little evidence is available on the number, distribution, or trend of evaluations on PRWs. Furthermore, there is no published evidence available that analyzes the characteristics of the patients who provide ratings on PRWs. Objective: The objective of the study was to analyze all physician evaluations that were posted on the German PRW, jameda in 2012. Methods: Data from the German PRW, jameda, from 2012 were analyzed and contained 127,192 ratings of 53,585 physicians from 107,148 patients. Information included medical specialty and gender of the physician, age, gender, and health insurance status of the patient, as well as the results of the physician ratings. Statistical analysis was carried out using the median test and Kendall Tau-b test. Results: Thirty-seven percent of all German physicians were rated on jameda in 2012. Nearly half of those physicians were rated once, and less than 2% were rated more than ten times (mean number of ratings 2.37, SD 3.17). About one third of all rated physicians were female. Rating patients were mostly female (60%), between 30-50 years (51%) and covered by Statutory Health Insurance (83%). A mean of 1.19 evaluations per patient could be calculated (SD 0.778). Most of the rated medical specialties were orthopedists, dermatologists, and gynecologists. Two thirds of all ratings could be assigned to the best category, "very good". Female physicians had significantly better ratings than did their male colleagues (P<.001). Additionally, significant rating differences existed between medical specialties (P<.001). It could further be shown that older patients gave better ratings than did their younger counterparts (P<.001). The same was true for patients covered by private health insurance; they gave more favorable evaluations than did patients covered by statutory health insurance (P<.001). No significant rating differences could be detected between female and male patients (P=.505). The likelihood of a good rating was shown to increase with a rising number of both physician and patient ratings. Conclusions: Our findings are mostly in line with those published for PRWs from the United States. It could be shown that most of the ratings were positive, and differences existed regarding sociodemographic characteristics of both physicians and patients. An increase in the usage of PRWs might contribute to reducing the lack of publicly available information on physician quality. However, it remains unclear whether PRWs have the potential to reflect the quality of care offered by individual health care providers. Further research should assess in more detail the motivation of patients who rate their physicians online.
WiSo-Import:2015-03-26:4429
Keywords: Internet; Patient satisfaction; Physician rating website; Public reporting; Quality of care

Auswirkungen des flächendeckenden Einsatzes von Mobile Stroke Units: das ProHTA-Simulationskonzept - Kriza, Christine; Djanatliev, Anatoli; Meier, Florian; Wahlster, Philip; Gantner-Bär, Marion; Hofmann, Bernd; German, Reinhard; Sedlmayr, Martin; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.auswir

Bewertung der Einsparpotenziale in der Arzneimitteltherapie durch Dosisanpassung an die Polymorphismen im Cychotrom P450 (Evaluation of economic savings in drug therapy by dose adjustment to polymorphisms in cytochrome P450) - Meier, Florian; Kontekakis, Antonis; Schöffski, Oliver (PharmacoEconomics German Research Articles, 2012)
<p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Objective <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> The cytochrome P450 superfamily is an important enzyme complex which aids in the metabolization of approximately 80% of pharmaceuticals currently on the market. Genetic variation leads to different phenotypes of metabolization: extensive metabolizer (EM), intermediate metabolizer (IM), poor metabolizer (PM) and ultra-rapid metabolizer (UM). Depending on polymorphism, different doses are appropriate. The information about 2D6, 2C9 and 2C19 is especially relevant from an economic point of view. The authors aim to determine how large the economic savings can be for the statutory health insurance by adapting the dose rate according to the CYP450 genotype. Therefore, they explored the top ten groups of the Anatomical Therapeutic Chemical (ATC) Classification System in sales in 2010. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Methods <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> To calculate potential savings, a formula was designed, which includes the relevant agents, the frequency in which polymorphisms occur, the average defined daily doses and their costs, the number of patients, and the average intake period. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Results <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> 36 appropriate agents were identified for calculation. They incurred a total cost of h2.3 billion for the statutory health insurance in 2010. The maximum saving potential lies in the ATC-group of psychoanaleptics, amounting to h96.1 million. Aripiprazol (h948.60), perphenazin (h352.40) and thiordiazin (€319.10) head the list of agents with the best saving potential per patient and treatment phase. Regarding the costs of diagnostic tests (€100 or €300), only four out of eight drugs are cost-covering. <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Conclusion <p class="Para" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 1.6; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.5em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px; color: rgb(51, 51, 51);"> Pharmacogenetic testing and subsequent dose optimization is partially efficient. Mainly for agents with high €/DDD (DDD: Defined Daily Dose) and long duration of treatment, positive cost-aspects have been calculated in total or on a per patient basis. For final economic appraisal, further information is needed, such as the effect on adverse drug reaction or synergy effects for multi-medicated patients. Finally, dose optimization based on genetic information is likely to be efficient for several agents.
WiSo-Import:2015-03-26:4183

Brust-CT als alternative Bildgebung im Brustkrebs-Screening in Deutschland: das ProHTA-Simulationskonzept - Meier, Florian; Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Leb, Ines; Schöffski, Oliver; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.brustc

Erlösquellen einer Notaufnahme - Meier, Florian; Bauer, K; Schöpke, T; Schöffski, Oliver (Das ZNA-Buch. Aufbau, Organisation und Management der Zentralen Notaufnahme, 2017)

Evaluations of dentists on a German physician rating Website: an analysis of the ratings. - Emmert, Martin; Halling, Frank; Meier, Florian (Journal of Medical Internet Research, 2015)
BACKGROUND Physician rating websites have been gaining in importance in both practice and research. However, no evidence is available concerning patients' ratings of dentists on physician rating websites. OBJECTIVE The aim of this study is to present a comprehensive analysis of the ratings of dentists on a German physician rating website over a 2-year period. METHODS All dentist ratings on a German physician rating website (Jameda) from 2012 and 2013 were analyzed. The available dataset contained 76,456 ratings of 23,902 dentists from 72,758 patients. Additional information included the overall score and subscores for 5 mandatory questions, the medical specialty and gender of the dentists, and the age, gender, and health insurance status of the patients. Statistical analysis was conducted using the median test and the Kendall tau-b test. RESULTS During the study period, 44.57% (23,902/53,626) of all dentists in Germany were evaluated on the physician rating website, Jameda. The number of ratings rose from 28,843 in 2012 to 47,613 in 2013, representing an increase of 65.08%. In detail, 45.37% (10,845/23,902) of dentists were rated once, 43.41% (10,376/23,902) between 2 and 5 times, and 11.21% (2681/23,902) more than 6 times (mean 3.16, SD 5.57). Approximately 90% (21,324/23,902, 89.21%) of dentists received a very good or good overall rating, whereas only 3.02% (721/23,902) were rated with the lowest scores. Better ratings were given either by female or older patients, or by those covered by private health insurance. The best-rated specialty was pediatric dentistry; the lowest ratings were given to orthodontists. Finally, dentists were rated slightly lower in 2013 compared to 2012 (P=.01). CONCLUSIONS The rise in the number of ratings for dentists demonstrates the increasing popularity of physician rating websites and the need for information about health care providers. Future research should assess whether social media, especially Web-based ratings, are suitable in practice for patients and other stakeholders in health care (eg, insurance providers) to reflect the clinical quality of car

Gesundheitsökonomische Evaluierung eines hypothetischen Biomarkers in einem Prostata-Screening-Szenario in Deutschland unter Anwendung eines hybriden Simulationsmodells - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Sedlmayr, Martin; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; German, Reinhard; Emmert, Martin (Tagungsband der 6. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.gesund

Health Economic Evaluation of a Contemplementary Biomarker for Hypothetical Prostate Cancer Screening in Germany - Meier, Florian; Niederländer, Charlotte; Djanatliev, Anatoli; Gantner-Bär, Marion; Höllthaler, Josef; Voigt, Wieland; Schöffski, Oliver; Kolominsky-Rabas, Peter; Emmert, Martin (Value in Health, 2013)
Prostate cancer (PCA) is the most common cancer in men worldwide. However, there is disagreement about the benefits of existing screening programs. This is mainly due to low specificity of currently utilized biomarkers. This can lead to both inappropriate medical treatment and increasing costs of care. For the future, many biotechnological developments are promising, but not all will be affordable for routine screening. The question is how much a complementary biomarker to prostate-specific antigen (PSA)-test may cost which would be applied to avoid false-positive result
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD7.health

Health economic impact of a pulmonary artery pressure sensor for heart failure telemonitoring: a dynamic simulation - Kolominsky-Rabas, Peter; Kriza, Christine; Djanatliev, Anatoli; Meier, Florian; Uffenorde, Steffen; Radeleff, Jannis; Baumgärtel, Philipp; Leb, Ines; Sedlmayr, Martin; Gaiser, Sebastian; Adamson, Phil (Telemedicine Journal and E-Health, 2016)
AIMS: Recently, a permanently implantable wireless system, designed to monitor and manage pulmonary artery (PA) pressures remotely, demonstrated significant reductions in heart failure (HF) hospitalizations in high-risk symptomatic patients, regardless of ejection fraction. The objectives of this study were to simulate the estimated clinical and economic impact in Germany of generalized use of this PA pressure monitoring system considering reductions of HF hospitalizations and the improvement in Quality of Life. MATERIALS AND METHODS: Based on the Prospective Health Technology Assessment approach, we simulated the potential of the widespread application of PA pressure monitoring on the German healthcare system for the period 2009-2021. RESULTS: This healthcare economic simulation formulated input assumptions based on results from the CHAMPION Trial, a multicenter, prospective, randomized controlled U.S. trial that demonstrated a 37% reduction of hospitalizations in persistently symptomatic previous HF patients. Based on these results, an estimated 114,800 hospitalizations would expected to be avoided. This effect would potentially save an estimated €522 million, an equivalent of 575 million, during the entire simulation period. CONCLUSION: This healthcare economic modeling of the PA pressure monitoring system's impact demonstrates substantial clinical and economic benefits in the German healthcare system.
EVALuna2:33966
Keywords: to appear

Individualized versus standardized risk assessment in patients at high risk for adverse drug reactions (IDrug) – study protocol for a pragmatic randomized controlled trial - Stingl, Julia; Kaumanns, Katharina; Claus, Katrin; Lehmann, Marie-Louise; Kastenmüller, Kathrin; Bleckwenn, Markus; Hartmann, Gunther; Steffens, Michael; Wirtz, Dorothee; Lechs, Ann-Kristin; Benda, Norbert; Meier, Florian; et al. (Bmc Family Practice, 2016)
Background Elderly patients are particularly vulnerable to adverse drug reactions, especially if they are affected by additional risk factors such as multimorbidity, polypharmacy, impaired renal function and intake of drugs with high risk potential. Apart from these clinical parameters, drug safety and efficacy can be influenced by pharmacogenetic factors. Evidence-based recommendations concerning drug-gene-combinations have been issued by international consortia and in drug labels. However, clinical benefit of providing information on individual patient factors in a comprehensive risk assessment aiming to reduce the occurrence and severity of adverse drug reactions is not evident. Purpose of this randomized controlled trial is to compare the effect of a concise individual risk information leaflet with standard information on risk factors for side effects. Methods/Design The trial was designed as a prospective, two-arm, randomized, controlled, multicenter, pragmatic study. 960 elderly, multimorbid outpatients in general medicine are included if they take at least one high risk and one other long-term drug (polymedication). As high risk “index drugs” oral anticoagulants and antiplatelets were chosen because of their specific, objectively assessable side effects. Following randomization, test group patients receive an individualized risk assessment leaflet evaluating their personal data concerning bleeding- and thromboembolic-risk-scores, potential drug-drug-interactions, age, renal function and pharmacogenetic factors. Control group patients obtain a standardized leaflet only containing general information on these criteria. Follow-up period is 9 months for each patient. Primary endpoint is the occurrence of a thromboembolic/bleeding event or death. Secondary endpoints are other adverse drug reactions, hospital admissions, specialist referrals and medication changes due to adverse drug reactions, the patients’ adherence to medication regimen as well as health related quality of life, mortality and resulting costs. Discussion Despite extensive evidence of risk factors for adverse drug reactions, there are few prospective trial data about an individualized risk assessment including pharmacogenetic information to increase patient safety. By conducting a health economic analysis, we will evaluate if the application of an individualized drug therapy in daily routine is cost-effective.
Keywords: Individualized medicine; Adverse drug reaction; Elderly; Pharmacogenetics; Polymedication; Drug interaction; ADR risk assessment; Clinical decision support system

Interne Abrechnungsmodelle der ZNA - Bauer, Kathrin; Brachmann, M; Meier, Florian; Schöffski, Oliver (Das ZNA-Buch. Aufbau, Organisation und Management der Zentralen Notaufnahme, 2017)

Leistungserbringer im deutschen Gesundheitswesen - Meier, Florian; Kast, Kristina; Schöffski, Oliver (Handbuch Gesundheitssoziologie, 2017)

Ökonomische Effekte durch den Einsatz von CardioMEMS bei herzinsuffizienten Patienten in Deutschland: das ProHTA-Simulationskonzept - Uffenorde, Steffen; Meier, Florian; Radeleff, Jannis; Djanatliev, Anatoli; Kriza, Christine; Baumgärtel, Philipp; Leb, Ines; Kolominsky-Rabas, Peter (Tagungsband der 7. Jahrestagung der Deutschen Gesellschaft für Gesundheitsökonomie, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.konomi

Physician choice making and characteristics associated with using physician-rating websites: cross-sectional study - Emmert, Martin; Meier, Florian; Pisch, Frank; Sander, Uwe (Journal of Medical Internet Research, 2013)
WiSo-Import:2015-03-26:4427

Potentially inappropriate medication in the elderly in Germany: an economic appraisal of the PRISCUS list - Pohl-Dernick, Katharina; Meier, Florian; Maas, Renke; Schöffski, Oliver; Emmert, Martin (BMC Health Services Research, 2016)
Background Several lists of potentially inappropriate medication (PIM) for elderly patients have been developed worldwide in recent years. Those lists intend to reduce prescriptions of drugs that carry an unnecessarily high risk of adverse drug events in elderly patients. In 2010, an expert panel published the PRISCUS list for the German drug market. This study calculates the amount of drug reimbursement for PIM in Germany and potential cost effects from the perspective of statutory health insurance when these are replaced by the substitutes recommended by the PRISCUS list. Methods Register-based data for the 30 top-selling drugs on the PRISCUS list in 2009 for patients greater than or equal to 65 years of age were provided by the Scientific Institute of the German Local Health Care Fund. We calculated the percentage of sales and defined daily doses for patients greater than or equal to 65 years of age compared with the total statutory health insurance population. Reimbursement costs for the recommended substitutions were estimated by considering different scenarios. Results In 2009, drug reimbursement for the 30 top-selling PIM prescribed to patients greater than or equal to 65 years of age were calculated to be €305.7 million. Prescribing the recommended substitution medication instead of PIM would lead to an increased total reimbursement cost for the German health care system ranging between from €325.9 million to €810.0 million. Conclusions The results show that the substitution of PIM by medication deemed to be more appropriate for the elderly comes along with additional costs. Consequently, there is no short-term incentive for doing so from a payer perspective. Future studies have to consider the long-term effects and other sectors.
Keywords: Potentially inappropriate medication; Elderly; Drug Reimbursement; PRISCUS; Reimbursement costs

Prospective Assessment of an innovative test for prostate cancer screening using the VITA process model framework - Gantner-Bär, Marion; Meier, Florian; Kolominsky-Rabas, Peter; Djanatliev, Anatoli; Metzger, Armin; Voigt, Wieland; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2014)
Healthcare innovations are crucial for enhancing patient treatment and a high-quality healthcare system. However, bringing new technologies, methods and procedures into the healthcare market is challenging. Enormous amounts of financial, personnel and organizational resources are required with no upfront certainty for the medical and economic benefit. A new and innovative approach uses interdisciplinary medical, technical and economic expertise to forecast effects of healthcare innovations already at the early research and concept phase of an idea and before major investments are made. A process model framework was developed to operationalize this structured assessment of healthcare innovations. The Visionary Iterative Tailored Approach (VITA) is based on conceptual modeling, simulation and health economics evaluation. Its application for the prospective assessment of an innovative prostate cancer screening is presented.<br
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD7.prospe

Public-private partnership as a solution for integrating genetic services into health care of countries with low and middle incomes. - Meier, Florian; Schöffski, Oliver; Schmidtke, Jörg (Journal of community genetics, 2013)
In recent years scientific progress has dramatically raised the potential of genetic services, but the actual benefits of these developments are not universally shared. In countries of low and middle incomes, improvements in genetic services frequently lag behind. Since this is generally caused by lack of resources and not by the lack of political will, the question arises, how can one most easily acquire the necessary capital to improve the health care in these areas. Public-private partnerships (PPPs) offer one approach to solve this issue, aiming at the inclusion of private enterprises in the realisation of public authority services. So far PPPs have been used exclusively in other health service areas. In this paper a first attempt is being made to discuss the feasibility of transferring the concept of PPP to genetic services, and consideration is given as to where the most promising starting point might be. We start by defining a multilevel structure that needs to be considered in providing comprehensive genetic care. We continue by explaining the concept of PPPs and their current types of implementation in medical services. We then examine how the PPP model could be applied to genetic services or sections thereof. We arrive at the conclusion that a likely starting point for PPP in genetic services is at the level of the infrastructure building service.

Screening for breast cancer with Breast-CT in a ProHTA simulation - Ruile, Georg; Djanatliev, Anatoli; Kriza, Christine; Meier, Florian; Leb, Ines; Kalender, Willi Alfred; Kolominsky-Rabas, Peter (Journal of Comparative Effectiveness Research, 2015)
Aims: The potential of dedicated Breast-CT is evaluated by simulating its impact onto the performance of the German breast cancer screening program. Attendance rates, cancer detection and economic implications are quantified. Methods: Based on a prospective health technology assessment approach, we simulated screening in different scenarios. Results: In the simulation, attendance rates increase from 54 to up to 72% due to reduced pain. Breast cancers will be detected earlier while nodal positives and distant recurrences decrease. Assuming no additional cost, cost savings of up to 55 million in one screening period are computed. Conclusion: The simulation indicates that earlier cancer detection, fewer unnecessary biopsies and less pain are potential benefits of Breast-CT resulting in cost savings and higher attendance.
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.IMMD7.screen
Keywords: breast cancer; computed tomography; health economics; health technology assessment; mammography screening; simulation

The direct costs of adverse drug events in emergency department admissions - Meier, Florian; Maas, Renke; Sonst, Anja; Patapovas, Andrius; Müller, Fabian; Plank-Kiegele, Bettina; Pfistermeister, Barbara; Schöffski, Oliver; Bürkle, Thomas; Dormann, Harald (19. Jahrestagung der Gesellschaft für Arzneimittelanwendungsforschung und Arzneimittelepidemiologie, 2012)
Background: Adverse drug events (ADE) are a health thread for patients and result in rising healthcare costs. Adverse events causing follow-up treatments claim the health insurance funds for prolonged diagnostics and treatment. Several German and international studies confirmed the economic impact, but an internationally accepted and standardized methodical approach to assess the effects has not been established so far. The aim of our study was to derive a portable measurement technique and to analyze the direct costs of community acquired adverse drug events (ADE) in patients with an emergency department (ED) admission and a subsequent hospital stay. Materials and Methods: We conducted a prospective observational study in a 749 bed tertiary care hospital with an annual ED census of more than 40,000 patients. The patient records of all emergencies were systematically analyzed by a team of emergency physicians, clinical pharmacologists and pharmacists for potential ADE. For hospitalized patients with an ADE we calculated the direct costs according to paragraph 21 of the Hospital Remuneration Act (KHEntgG) taking data from the hospital information system (HIS). Results: Among 752 patients we identified 106 patients (mean age: 70.8 years) with an inpatient stay (mean length of stay: 7.5 days) having a total of 153 ADE. This subgroup caused mean costs of 2,968.49 €. Extrapolating these costs for Germany we estimate an amount of € 1.46 bn to be spent for hospitalized patients with ADE annually. Among the patients with ADE cases with cardiovascular disorders and gastrointestinal diseases were dominating. Compared with typical prescription quantities antipsychotic drugs cause frequently ADE and dopaminerge substances lead to extensive hospitalization. The most common drugs associated with ADE were antipsychotics (11.9%), platelet inhibiting factors (10.8%) and ACE blockers (8.7%). Most events were predictable (96.7%), almost 65.4% of the observed ADE were judged to be preventable. Conclusion: Since there is no gold standard for the evaluation of ADE-costs, we recommend the intensive pharmacovigilance method described here in combination with standardized cost data of hospital reimbursement as an appropriate approach for inpatients. ADE were common, often preventable and associated with significant costs. Thus, many stakeholders could benefit from effective and cost efficient prevention strategies for ADE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.infome.thedir

The prevalence and prognostic significance of near syncope and syncope: a prospective study of 395 cases in an emergency department (the SPEED study) - Greve, Yvonne; Geier, Felicitas; Popp, Steffen; Bertsch, Thomas; Singler, Katrin; Meier, Florian; Smolarsky, Alexander; Mang, Harald; Mueller, Christian; Christ, Michael (Deutsches Ärzteblatt international, 2014)
The prognostic significance of near-syncope has not yet been adequately characterized.We collected prospective data on a consecutive series of patients seen in an emergency department with syncope (brief loss of consciousness, usually with loss of muscle tone) or near-syncope (a feeling that syncope is about to occur, but without actual loss of consciousness or muscle tone). We report on the prevalence, etiology, and prognosis of such events (the SPEED study). Patients were followed up at 30 days and at 6 months after the event.From 17 July to 31 October 2011, 395 patients were seen in the emergency department for a chief complaint of syncope or near-syncope (3% of all emergency patients). Their median age was 70 years, and 55% were men. 62% had experienced syncope, and 38% near-syncope. The patients with near-syncope were younger than those with syncope ( 63 vs. 72 years, p < 0.014) and were also more commonly male (63% vs. 49%, p = 0.006). The two patient groups did not differ significantly with respect to their measured laboratory values and vital parameters or their accompanying medical conditions. Hospitalizations were more common for syncope than for near-syncope (86% vs. 70%, p < 0.001). Etiologies were similarly distributed in the two patient groups, with the main ones being reflex syncope, orthostatic syncope, cardiac syncope, and syncope of uncertain origin. In all, 123 of 379 patients (32%) had further undesired events within 30 days of the event. Multivariable logistic regression revealed that age, heart rate, and renal dysfunction were independent predictors of undesired events, while the type of syncope was not.Patients with near-syncope do not differ to any large extent from patients with syncope with respect to the features studied. The diagnostic evaluation should be similar for patients in the two groups.
EVALuna2:10506

What do patients say about their physicians? an analysis of 3000 narrative comments posted on a German physician rating website. - Emmert, Martin; Meier, Florian; Heider, Ann-Kathrin; Dürr, Christoph; Sander, Uwe (Health policy (Amsterdam, Netherlands), 2014)
BACKGROUND Physician rating websites (PRWs) could be shown to have an impact on physician choice making. However, little research has been carried out to assess the content and nature of narrative comments. OBJECTIVE The aim of this study was to explore the concerns of patients who commented on physician care and to address and enhance patient satisfaction. METHODS Content analysis of 3000 randomly selected narrative comments from the German PRW, jameda, from 2012. We therefore developed a theoretical categorization framework addressing physician, staff, and practice related patient concerns. FINDINGS In total, 50 sub-categories addressing the physician (N=20), the office staff (N=13), and the practice (N=17) were derived from the content of all comments. The most frequently mentioned concerns were assessing the professional competence of the physician (63%, N=1874) and friendliness of the physician (38%, N=1148). Thereby, 80% of all comments (mean length 45.3 words ± 42.8) were classified as positive, 4% as neutral and 16% as negative. CONCLUSION Users of the German PRW, jameda, are mostly satisfied with their physicians. However, physicians should focus on the time spent with the patients, waiting time, as well as on taking the patients more seriously.

ZNA als Cost Center - Meier, Florian; Bauer, K; Schöffski, Oliver (Das ZNA-Buch. Aufbau, Organisation und Management der Zentralen Notaufnahme, 2017)

Zur Ökonomie ambulanter Notaufnahmepatienten. Untersuchung der Deckungsbeiträge in Abhängigkeit von Dringlichkeitskategorien, Leitsymptomen und Diagnosen - Meier, Florian; Bauer, K; Schöffski, Oliver; Schöpke, Timo; Dormann, Harald (Notfall und Rettungsmedizin, 2016)
Hintergrund In Anbetracht der defizitären finanziellen Lage von deutschen Notaufnahmen wurde die wirtschaftliche Situation einer Zentralen Notaufnahme (ZNA) bei der Versorgung ambulanter Fälle untersucht. Hierbei kamen verschiedene medizinische Kategorisierungssysteme zum Einsatz − mit dem Ziel, die mit der Behandlung ambulanter Notfallpatienten einhergehenden Deckungsbeiträge insbesondere aus der ex ante-Sicht zu beleuchten. Methodik Auf Grundlage der Kostenträgerrechnungsmethodik des Instituts für das Entgeltsystem im Krankenhaus (InEK) wurden die fallbezogenen Ist-Kosten auf Vollkostenbasis für 16.833 ambulante GKV-Patienten der ZNA des Klinikums Fürth aus dem Jahr 2013 ermittelt und im Hinblick auf Dringlichkeit (ESI), Leitsymptome (CEDIS) und Diagnosen (ICD) analysiert. Ergebnisse Den durchschnittlichen Fallkosten von 113,46 € stehen mittlere Fallerlöse von 36,21 € gegenüber, woraus sich ein Fehlbetrag von − 77,26 € pro Fall errechnet. Für keine der untersuchten Patientengruppen kann die Behandlung gewinnbringend bzw. zumindest kostendeckend erbracht werden. Diskussion Der Ressourcenverbrauch bei der Behandlung eines Notaufnahmepatienten hängt stark von den medizinischen Entscheidungen ab, die ex ante, d. h. basierend auf Leitsymptom und Dringlichkeitskategorie, gefällt werden. In Anbetracht der Ergebnisse der vorliegenden Studie, der zufolge weder dringliche Patienten mit kritischen Leitsymptomen noch Fälle mit unkritischen Symptomen und geringer Dringlichkeitsstufe kostendeckend behandelt werden können, sind die derzeitigen Vergütungsstrukturen kritisch zu hinterfragen.
Keywords: Notaufnahme; Ambulante Behandlung; Kostenträgerrechnung; Krankenkassenvergütung; Ressourcenverbrauch